Comparison between cerebroplacental ratio and umbilicocerebral ratio in predicting adverse perinatal outcome at term. (September 2020) - Di Mascio, Daniele; Rizzo, Giuseppe; Buca, Danilo; D'Amico, Alice; Leombroni, Martina; Tinari, Sara; Giancotti, Antonella; Muzii, Ludovico; Nappi, Luigi; Liberati, Marco; D'Antonio, Francesco
Abstract: Objective: Cerebroplacental ratio (CPR) has been associated with adverse perinatal outcome irrespective of fetal weight. More recently, it has been proposed that the ratio between umbilical and middle cerebral artery pulsatility index, the umbilicocerebral ratio (UCR) had a higher diagnostic accuracy compared to CPR in predicting adverse outcome. The aim of the study was to compare the diagnostic accuracy of CPR and UCR in predicting adverse perinatal outcome in the third trimester of pregnancy. Study design: Secondary analysis of prospective study carried out in a dedicated research ultrasound clinic in a single tertiary referral center over a one-year period. Inclusion criteria were consecutive singleton pregnancies between 36 + 0 and 37 + 6 weeks of gestation. Exclusion criteria were multiple gestations, pregnancies affected by structural or chromosomal anomalies, maternal medical complications or drugs intake and abnormal Doppler waveform in the UA, defined as PI>95th or absent/end diastolic flow. All women were pre-screened at 28–32 weeks of gestation in order to rule out signs of early fetal growth restriction. The primary outcome was to compare the diagnostic performance of CPR and UCR in detecting the presence of fetuses affected by a composite adverse outcome. Results: Mean CPR (1.35 ± 0.39 vs 1.85 ± 0.58, p < 0.001) was significantly lower while mean UCR (0.78 ± 0.25 vs 0.58 ± 0.20, p = 0.001) was significantly higher in pregnancies experiencing compared to those not experiencing composite adverse outcome. There was no difference between CPR and UCR in predicting adverse perinatal outcome in the third trimester of pregnancy and both showed a very low diagnostic accuracy. CPR had an AUC of 0.51 (95 % CI 0.43−0.58) while UCR had an AUC of 0.51 (95 % CI 0.43−0.58) in predicting composite adverse outcome. Likewise, there was no difference in the diagnostic accuracy of CRP (AUC: 0.600, 95 % CI 0.36−0.83) and UCR (AUC: 0.589, 95 % CI 0.35−0.83) when considering only SGA fetuses. Conclusions: A low CPR and a high UCR are significantly associated with adverse perinatal outcome in singleton pregnancies at term. There was no difference between CPR and UCR in predicting perinatal outcome. Despite this, the diagnostic accuracy of both these parameters is too poor to advocate for their use as a screening tool of perinatal impairment at term, unless specific indications, such as SGA or FGR, have been identified.